Persistent left superior vena cava connected through the left upper pulmonary vein to the left atrium: an unusual pathway for paradoxical embolization and a rare cause of recurrent transient ischaemic attack - Hutyra, Martin; Skala, Tomas; Sanak, Daniel; Novotny, Josef; Köcher, Martin; Taborsky, Milos (European journal of echocardiography, 2010)
Ischaemic stroke, especially in the younger population, is an important cause of morbidity and mortality. When compared with the older population, the underlying aetiology of stroke in the young includes higher rates of cardioembolic disease and congenital heart anomalies. Paradoxical embolism may be an important cause of ischaemic cerebral events, which has to be ruled out in patients with no other evident stroke aetiology. A persistent left superior vena cava (PLSVC) that drains into the left atrium is a very rare congenital anomaly occurring in postnatal life and may be the cause of embolic events such as ischaemic stroke with potentially devastating consequences. For diagnostic purposes, we recommend the use of contrast transthoracic and transesophageal echocardiography with contrast agent application through the left arm peripheral intravenous line, which makes it possible to ascertain the presence of a right-to-left shunt. Computed tomography of the chest is recommended for a PLSVC with atypical left atrial drainage confirmation. Consequent endovascular occlusion of the PLSVC is feasible and can be performed with minimal procedural risk. If this cause of paradoxical embolism is not taken into consideration, the first manifestation of this clinical entity could be underestimated, increasing the likelihood of ischaemic stroke recurrence with potentially disabling or fatal consequences. We report the diagnosis and successful endovascular repair of this anomaly. This case report also aims to highlight the importance of close collaboration between neurologists, cardiologists and radiologists needed for accurate identification of stroke aetiology in young patients.
Keywords: Echocardiography; terapeutická embolizace; Female; Humans; Ischemic Attack, Transient; venae pulmonales; magnetická rezonanční tomografie; tranzitorní ischemická ataka; lidé; echokardiografie; kontrastní látky; vena cava superior; Vena Cava, Superior; ženské pohlaví; počítačová rentgenová tomografie; Heart Atria; rizikové faktory; Embolization, Therapeutic; Pulmonary Veins; Magnetic Resonance Imaging; Embolism, Paradoxical; Contrast Media; srdeční síně; Risk Factors; dospělí; Diagnosis, Differential; Adult; paradoxní embolie; diferenciální diagnóza; Tomography, X-Ray Computed